The in vivo mechanism of action of CD20 monoclonal antibodies depends on local tumor burden - Boross, Peter (Ferrata Storti Foundation, 2011)
BACKGROUND: CD20 monoclonal antibodies are widely used in clinical practice. Antibody-dependent cellular cytotoxicity, complement-dependent cytotoxicity and direct cell death have been suggested to be important effector functions for CD20 antibodies. However, their specific contributions to the in vivo mechanism of action of CD20 immunotherapy have not been well defined. DESIGN AND METHODS: Here we studied the in vivo mechanism of action of type I (rituximab and ofatumumab) and type II (HuMab-11B8) CD20 antibodies in a peritoneal, syngeneic, mouse model with EL4-CD20 cells using low and high tumor burden. RESULTS: Interestingly, we observed striking differences in the in vivo mechanism of action of CD20 antibodies dependent on tumor load. In conditions of low tumor burden, complement was sufficient for tumor killing both for type I and type II CD20 antibodies. In contrast, in conditions of high tumor burden, activating FcγR (specifically FcγRIII), active complement and complement receptor 3 were all essential for tumor killing. Our data suggest that complement-enhanced antibody-dependent cellular cytotoxicity may critically affect tumor killing by CD20 antibodies in vivo. The type II CD20 antibody 11B8, which is a poor inducer of complement activation, was ineffective against high tumor burden. CONCLUSIONS: Tumor burden affects the in vivo mechanism of action of CD20 antibodies. Low tumor load can be eliminated by complement alone, whereas elimination of high tumor load requires multiple effector mechanisms.